Pedagogía Reggio Emilia en el desarrollo del aprendizaje integral de los niños de educación inicial II - Angulo Cornejo, Cinthia Michelle (2024)
Reggio Emilia Pedagogy is an educational approach recognized for its emphasis on creativity, active participation and the construction of knowledge, therefore, the present research work aims to analyze the contributions of Reggio Emilia Pedagogy to the development of comprehensive learning of the children of sublevel II of the "León de Febres Cordero" Educational Unit during the period 2023-2024. To carry out this analysis, a qualitative approach with a descriptive research methodology was used. The synthetic analytical method was used to unravel the key elements of Reggio Emilia Pedagogy and its application in the learning process of children. Data collection included classroom observations, a survey with educators and representatives, as well as the analysis of educational material used. The results revealed the positive influence of Reggio Emilia Pedagogy on the comprehensive development of children in sublevel II, highlighting the best practices to adapt this approach to the specific characteristics of children in this sublevel. From the results obtained, conclusions were drawn up that summarize the contributions of Reggio Emilia Pedagogy in the specific context of the "León de Febres Cordero" Educational Unit, serving as a basis for practical recommendations and future research, with the aim of continuous improvement. the quality of the comprehensive learning of children at this sublevel.